Can we improve parents’ management of their children’s postoperative pain at home? - Chorney, Jill MacLaren (Pulsus Group Inc, 2014)
BACKGROUND: Thousands of children undergo surgery each year, and a shift toward same-day surgeries and decreased lengths of hospital stay results in parents being increasingly responsible for their child’s postoperative care. Recent studies have tested interventions designed to improve parent management of their children’s postoperative pain at home, but progress in this area has been limited by a lack of synthesis of these findings. OBJECTIVE: To conduct a systematic review of interventions aimed at improving parent management of children’s postoperative pain at home. METHODS: Articles evaluating interventions to improve management of their children’s postoperative pain were identified using a library scientist-designed search strategy applied in EMBASE, PubMed, CINAHL and PsycINFO. Two independent raters assessed each study for eligibility and extracted data. RESULTS: Of the 147 articles identified for the review, eight met the inclusion criteria. Interventions included pain education, training in pain assessment, education on distraction, instruction in around-the-clock dosing and nurse coaching. Overall, results of comparisons of pain intensity and analgesic administration were modest. The intervention with the largest effect size was instruction in around-the-clock dosing, either alone or in combination with nurse coaching. Results of studies investigating pain assessment, pain education and distraction trials revealed small to medium effect sizes. CONCLUSIONS: Results of trials investigating interventions to improve parent management of their children’s postoperative pain at home were modest. Future studies should further examine barriers and facilitators to pain management to design more effective interventions.